1997
DOI: 10.1111/j.1600-0528.1997.tb00957.x
|View full text |Cite
|
Sign up to set email alerts
|

Edentulousness and its rehabilitation over a 10‐year period in a Finnish urban area

Abstract: In 1977 78, a baseline study group of 449 Finnish adults aged 30 years and over was examined in an urban area with a very high supply of dental services. The follow-up study in 1988 represents longitudinal data on 297 of these adults. In 1989 a new sample of persons aged 30-39 years was also obtained to provide cross-sectional information comparable to that of the corresponding age group in the 1977-78 survey. At baseline in 1977-78, the prevalence of total tooth loss was 19.4% for adults aged 30 years and ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The findings of this present study point to a gender inequality in edentulism that is in line with findings of previous studies reporting higher respective values for women (22, 28, 29). Women probably lose their teeth and become edentulous at an earlier age (30, 31).…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this present study point to a gender inequality in edentulism that is in line with findings of previous studies reporting higher respective values for women (22, 28, 29). Women probably lose their teeth and become edentulous at an earlier age (30, 31).…”
Section: Discussionsupporting
confidence: 93%
“…Hugoson et al (2005) recorded 0% prevalence for edentulism in people below the age of 60 in one Swedish city in 2003. Edentulism was observed in 0.8% of 30–39‐year‐old subjects in Finland in 1989 (Hiidenkari et al 1997), whereas no edentulism was found in a sample of 35–44‐year‐old French subjects in 1994 (Hescot et al 1997), and similar was the case in 35‐year‐old Swedes (Axelsson et al 1998). Sixteen percent of the 65–74‐year‐old French population were edentulous (Bourgeois et al 1995).…”
Section: Resultsmentioning
confidence: 91%
“…On the other hand, a decline in the tooth loss can be verified in developed countries in the last years [7, 11, 12], which can be explained by preventive programs and higher accessibility to the oral health care that have been decreasing the extractions [13, 14]. Brazil is a country in development progress (underdeveloped), and some studies verified the prevalence of tooth extractions in Brazilians [4, 810, 15, 16], but few of them have verified the reasons for the tooth mortality in this population.…”
Section: Introductionmentioning
confidence: 99%